Whole-school collaboration for social skill development in character education - R. Rafiqah; Iis Siti Aisyah; Agus Tinus; Peter Adewale (Research and Development in Education (RaDEn), 2025)
Social skills are pivotal to holistic education, yet character education initiatives in Indonesia are often carried mainly by school counselors. This study examined how a whole-school approach integrating counselors, teachers, and administrators strengthens students' social skills through character education. A sequential explanatory mixed-methods design was used at SMA Negeri 4 Sampit (Central Kalimantan). Interviews, classroom observations, and document review involved the principal, vice principal, counselor, and two subject teachers, followed by a 14-item social-skills questionnaire completed by 183 students (grades X–XII). Qualitative data were analyzed using Miles, Huberman, and Saldaña's interactive model; quantitative data used descriptive statistics. Counselors promoted empathy and reflection through individual counseling; teachers applied role play, restitution triangle, and classroom agreements; administrators supported policies and resources. Overall, 92% of students demonstrated high/very high social skills, with empathy, communication, and cooperation strongest, while conflict resolution and self-management were moderate. Collaborative, role-complementary whole-school character education appears effective, but structured interventions are needed to improve conflict resolution and self-management.